Cold flow experiments in an entrained flow gasification reactor with a swirl-stabilized pulverized biofuel burner. (October 2016) - Göktepe, Burak; Saber, Ammar Hazim; Gebart, Rikard; Lundström, T. Staffan
Highlights: Two-phase particle image velocimetry technique was adopted to pulverized biomass-air flows over a range of swirl numbers. The pattern of both particle and air flows were mapped in the near-field of the burner exit. The biomass particles in the fluid decelerated the carrier air flow, compared to the single phase flow. Swirl increased the entrainment rate of both the particle and the carrier air flows. Abstract: Short particle residence time in entrained flow gasifiers demands the use of pulverized fuel particles to promote mass and heat transfer, resulting high fuel conversion rate. The pulverized biomass particles have a wide range of aspect ratios which can exhibit different dispersion behavior than that of spherical particles in hot product gas flows. This results in spatial and temporal variations in temperature distribution, the composition and the concentration of syngas and soot yield. One way to control the particle dispersion is to impart a swirling motion to the carrier gas phase. This paper investigates the dispersion behavior of biomass fuel particles in swirling flows. A two-phase particle image velocimetry technique was applied to simultaneously measure particle and gas phase velocities in turbulent isothermal flows. Post-processed PIV images showed that a poly-dispersed behavior of biomass particles with a range of particle size of 112–160 µm imposed a significant impact on the air flow pattern, causing air flow decelerated in a region of high particle concentration. Moreover, the velocity field, obtained from individually tracked biomass particles showed that the swirling motion of the carrier air flow gives arise a rapid spreading of the particles.